Effect of trimetazidine combined with perindopril on NT-proBNP level in rats with dilated cardiomyopathy - Lin, Jinhai; Zhong, Bin; Yan, Jinling; Chen, Lili (Cellular and Molecular Biology, 2020)
This experiment aimed to study the effect of trimetazidine combined with perindopril on NT-proBNP levels in rats with dilated cardiomyopathy (DCM). 40 SD rats were selected and 10 rats were randomly selected to continue to be fed as the blank group. The other 30 rats were injected with adriamycin to establish the DCM rat model. Then they were divided into 3 groups, namely control group (without any drug intervention), trimetazidine group (with trimetazidine single-agent intervention) and combination drug group (with trimetazidine combined with perindopril intervention), with 10 DCM rats in each group. After 4 weeks of intervention, left ventricular ejection fraction (LVEF), left ventricular end-diastolic dimension (LVEDD) and left ventricular end-systolic diameter (LVESD) of rats were measured by echocardiography. The changes of plasma brain natriuretic peptide (BNP) level and n-terminal pro-brain natriuretic peptide (NT-proBNP) were detected by ELISA. RT-PCR was used to detect the regulation of angiotensin II type 1 receptor (AT1Rs) and lamin A mRNA expression in rat myocardium. After the intervention, the LVEF%, LVEDD and LVESD measured values of the rats in the combination drug group were significantly better than those in the trimetazidine group and the control group (P< 0.05). The BNP, NT-proBNP and AT1Rs levels of the rats in the combination drug group were significantly lower than those in the trimetazidine group and the control group. The difference was statistically significant (p< 0.05). The lamin A expression of the rats in the combination drug group was significantly higher than that in the trimetazidine group and the control group. The difference was statistically significant (P< 0.05). Compared with trimetazidine single-agent, trimetazidine combined with perindopril can significantly improve the cardiac function of rats with dilated cardiomyopathy, reduce the serum NT-proBNP level and improve the expression of AT1Rs and lamin A in rats.